2014
DOI: 10.1177/0733464814535484
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers’ Knowledge of Delirium and Preferred Modalities for Receipt of Information

Abstract: Delirium is a life-threatening, frequently reversible condition that is often a sign of an underlying health problem. In-hospital mortality alone for older adults with delirium ranges from 25% to 33%. Early recognition of delirium is critical because prolonged duration poses a greater risk of poor functional outcomes for older adults. Family caregivers, who are familiar with the older adult's usual behaviors, are most likely to recognize delirium symptoms but might dismiss them as due to aging. It is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…A little more than half of the participants minimally know that the fall of the aged is a frequent event and that it is at risk, identifying some causes and consequences of falls and referring to certain measures to prevent them. This result is compatible with those of other studies in which the knowledge about fall prevention presented by informal elderly caregivers was incomplete or considered minimal (25) and superficial (26) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A little more than half of the participants minimally know that the fall of the aged is a frequent event and that it is at risk, identifying some causes and consequences of falls and referring to certain measures to prevent them. This result is compatible with those of other studies in which the knowledge about fall prevention presented by informal elderly caregivers was incomplete or considered minimal (25) and superficial (26) .…”
Section: Discussionsupporting
confidence: 92%
“…Only two studies with elderly caregivers focused on falls and their prevention were conducted, but the objective was to investigate only the caregivers' knowledge. In one of the studies, the results showed that less than a half of the caregivers (42.7%) reported having knowledge about how to reduce the occurrence of falls, and 48.3% considered that the prevention of the event is possible (25) . In another study, the authors found that the knowledge that caregivers had about the prevention of falls of the elderly was superficial because they had not received adequate guidance (26) .…”
Section: Introductionmentioning
confidence: 99%
“…Family caregivers, who are familiar with the older adult's usual behaviors, are likely partners in early recognition of delirium. However, family caregivers might attribute delirium symptoms to normal aging or dementia (Bull, ; Bull, Boaz, & Sjostedt, ; Toye, Matthews, Hill, & Maher, ).…”
Section: Introductionmentioning
confidence: 99%
“…to normal aging or dementia (Bull, 2011;Bull, Boaz, & Sjostedt, 2014;Toye, Matthews, Hill, & Maher, 2014). The findings of descriptive studies indicate that family caregivers experience anxiety, fear, and distress when faced with older adults who have delirium symptoms (Bruera et al, 2009;Toye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses lack of familiarity with an older adult's usual behaviors (i.e., cognitive baseline) might contribute to the difficulty in recognizing delirium. Family members who are familiar with an older adult's usual behaviors are more likely to recognize delirium symptoms and could be vital partners in early recognition of symptoms but often lack knowledge of delirium, its symptoms, and the importance of contacting the older adult's health care provider when symptoms occur (Bull, 2011;Bull, Boaz, & Sjostedt, 2014;Otani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%